Impact of surgeon and anaesthesiologist sex on patient outcomes after cardiac surgery: a population-based study - Vincent Chan; Anan Bader Eddeen; Louise Y. Sun; Douglas S. Lee; Thierry G. Mesana; Cole Etherington (BMJ Open)
Background Effective teamwork between anaesthesiologists and surgeons is essential for optimising patient safety in the cardiac operating room. While many factors may influence the relationship between these two physicians, the role of sex and gender have yet to be investigated.Objectives We sought to determine the association between cardiac physician team sex discordance and patient outcomes.Design We performed a population-based, retrospective cohort study.Participants and setting Adult patients who underwent coronary artery bypass grafting (CABG) and/or aortic, mitral or tricuspid valve surgery between 2008 and 2018 in Ontario, Canada.Primary and secondary outcome measures The primary outcome was all-cause 30-day mortality. Secondary outcomes included major adverse cardiovascular events at 30 days and hospital and intensive care unit lengths of stay (LOS). Mixed effects logistic regression was used for categorical outcomes and Poisson regression for continuous outcomes.Results 79 862 patients underwent cardiac surgery by 98 surgeons (11.2% female) and 279 anaesthesiologists (23.3% female); 19 893 (24.9%) were treated by sex-discordant physician teams. Physician sex discordance was not associated with overall patient mortality or LOS; however, patients who underwent isolated CABG experienced longer hospital LOS when treated by an all-male physician team as compared with an all-female team (adjusted OR=1.07; p=0.049). When examining the impact of individual physician sex, the length of hospital stay was longer when isolated CABG procedures were attended by a male surgeon (OR=1.10; p=0.004) or anaesthesiologist (OR=1.02; p=0.01).Conclusions Patient mortality and length of stay after cardiac surgery may vary by sex concordance of the attending surgeon–anaesthesiologist team. Further research is needed to examine the underlying mechanisms of these observed relationships.